Damage progression in thermal barrier coating systems during thermal cycling: A nano-mechanical assessment. (15th March 2019) - Bolelli, Giovanni; Righi, Maria Grazia; Mughal, Muhammad Zeeshan; Moscatelli, Riccardo; Ligabue, Omar; Antolotti, Nelso; Sebastiani, Marco; Lusvarghi, Luca; Bemporad, Edoardo
Abstract: This paper studies how the nano-mechanical properties of thermal barrier coatings (TBCs) vary during thermal cycling, as a way to shed new light on their failure mechanisms. In particular, high-throughput nanoindentation revealed the evolution of hardness and elastic modulus distributions of plasma-sprayed yttria-stabilized zirconia (YSZ) top layers. The evolution of fracture toughness of the YSZ layers and the thermally grown oxide (TGO) formed onto the vacuum plasma-sprayed NiCoCrAlY bond coat were investigated by nanoindentation micro-pillar splitting. The TGO fracture toughness increases up to ≈2.5–3.5 MPa√m at the early stages of thermal cycling, followed by a rapid decrease to ≈2.0 MPa√m after a critical TGO thickness of ≈5 μm is reached. Consequently, interface damage is initially limited to short cracks within the YSZ material. As TGO thickness exceeds the critical threshold, multiple cracks originate within the TGO and join through the YSZ to form long delamination cracks. Joining is favoured by a simultaneous loss in YSZ strength, testified by a decrease in the nanomechanical properties (hardness, elastic modulus) of both high- and low-porosity top coats. This is due to microstructural changes occurring because of the continuous interplay between sintering and thermal shock cracking in the YSZ layers. Graphical abstract: Unlabelled Image Highlights: Nanomechanical properties of thermal barrier coatings were measured by high-speed nanoindentation and pillar splitting During thermal cycling, delamination damage progresses slowly as long as the bond coat forms a dense, tough oxide scale The fracture toughness of the thermally grown oxide scale drops when its thickness exceeds a 5-μm threshold Severe delamination damage starts from the embrittled thermally grown oxide and propagates across the zirconia top coat Such propagation is favoured by a simultaneous drop in top coat strength, due to accumulated microstructural alterations